THE JOURNEY OF MANAGERIAL ACCOUNTING RESEARCH IN SINTA 4-INDEXED JOURNALS - Tambunan, Sihar Tigor Benjamin; Widyaningdyah, Agnes Utari (Jurnal Akuntansi Kontemporer, 2024)
Research Purposes. This study uses a bibliographical approach to describe managerial accounting research (MAR) intention in Indonesia. The research materials are pertinent publications that appeared in SINTA 4-indexed journals between 2011 and 2022. Research Methods. Relevant articles are filtered based on several selection criteria at the Indonesia National Indexer (SINTA), journals, and articles. The metadata of the articles is tidied via Zotero reference management software. The output is CSV and RIS files. MS Excel and Tableau processed CSV files for visualization and qualitative analysis purposes, and RIS files were analyzed by VOSviewer software to create research network maps based on keyword occurrences. Several reputable international journals are used as a comparison.Research Results and Findings. In 2011-2022, 21 of 441 SINTA 4-indexed journals contained 129 articles (6% of 2,300) on managerial accounting topics. These topics form six research clusters with highly varied occurrences, links, intensities, and publication periods. Sustainability-related issues are in the first cluster. In general, SINTA 4-indexed journals in Indonesia, including accounting-specific journals,  have not placed managerial accounting as a particular priority. This research produces a bibliographic map of managerial accounting research in the 2011-2012 period, which can be used as a reference for further research, as well as contextual development of managerial accounting practices.